2012
DOI: 10.11646/zootaxa.3368.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Two newly recorded invasive alien ascidians (Chordata, Tunicata, Ascidiacea) based on morphological and molecular phylogenetic analysis in Korea

Abstract: We report five alien ascidians with some distinct features that were investigated from August 2009 to October 2011 in Korea, among which Ascidiella aspersa (Müller, 1776) belonging to family Ascidiidae of order Phlebobranchia and Molgula manhattensis (De Kay, 1843) belonging to family Molgulidae of order Stolidobranchia are newly discovered invasive species. These ascidians were identified and their phylogenetic relationships were clarified through molecular analysis using about 680 bp of nuclear 18S rDNA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Sequences obtained from GenBank and BOLD System databases were included in the analysis for comparison and as outgroups (Stach and Turbeville 2002;Kurabayashi et al 2003;Monniot et al 2011;Pyo et al 2012;López-Legentil et al 2015;Turon et al 2016). Once aligned using the BioEdit program 7.0.5.3 (Hall 1999), sequences were collapsed into haplotypes; the number of polymorphic sites and haplotypes were calculated using the program DNAsp 6 (Rozas et al 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Sequences obtained from GenBank and BOLD System databases were included in the analysis for comparison and as outgroups (Stach and Turbeville 2002;Kurabayashi et al 2003;Monniot et al 2011;Pyo et al 2012;López-Legentil et al 2015;Turon et al 2016). Once aligned using the BioEdit program 7.0.5.3 (Hall 1999), sequences were collapsed into haplotypes; the number of polymorphic sites and haplotypes were calculated using the program DNAsp 6 (Rozas et al 2017).…”
Section: Methodsmentioning
confidence: 99%
“…To date, most studies have focused on cataloguing the exotic species observed in a given location or harbor (e.g. Arenas et al 2006 ; Callahan et al 2010 ; Carman et al 2010 ; Sephton et al 2011 ; Pyo et al 2012 ); while a surprisingly low number of studies have explored the links between these harbors, including patterns of species turnover (beta-diversity), harbor type (recreational, fishing, commercial or mixtures thereof), or temporal or geographic trends (e.g. Lambert and Lambert 2003 ; Cohen et al 2005 ; Grey 2009a ).…”
Section: Introductionmentioning
confidence: 99%
“…In South Korea, the species was recognized firstly in 2010 from cool-, mid-, and warm-temperate zones by Pyo et al (2012). However, we suggest the possibility in this paper that the Korean coastline was actually already inhabited by this species in the 1990s.…”
Section: Introductionmentioning
confidence: 59%